2016
DOI: 10.1038/srep25904
|View full text |Cite
|
Sign up to set email alerts
|

Targeted next-generation sequencing for the detection of ciprofloxacin resistance markers using molecular inversion probes

Abstract: Antibiotic resistance (AR) is an epidemic of increasing magnitude requiring rapid identification and profiling for appropriate and timely therapeutic measures and containment strategies. In this context, ciprofloxacin is part of the first-line of countermeasures against numerous high consequence bacteria. Significant resistance can occur via single nucleotide polymorphisms (SNP) and deletions within ciprofloxacin targeted genes. Ideally, use of ciprofloxacin would be prefaced with AR determination to avoid ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 41 publications
2
26
0
Order By: Relevance
“…Although this enrichment method has been shown to increase the sensitivity of metagenomic detec tion in research settings, especially for viruses, it has yet to be used routinely for clinical diagnosis. A promising appli cation of this approach may be the enrichment of clinical samples for characterization of antibiotic resistance 23 , a considerable problem in hospitals and the primary focus of the US National Action Plan for Combating Antibiotic Resistant Bacteria 53 . However, drawbacks of capture probe enrichment, compared with untargeted approaches for infectious disease diagnosis, include a bias towards tar geted microorganisms, added steps, increased costs and long hybridization times (24-48 hours) as a result of the additional processing needed for maximal efficiency.…”
Section: Seroconversionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this enrichment method has been shown to increase the sensitivity of metagenomic detec tion in research settings, especially for viruses, it has yet to be used routinely for clinical diagnosis. A promising appli cation of this approach may be the enrichment of clinical samples for characterization of antibiotic resistance 23 , a considerable problem in hospitals and the primary focus of the US National Action Plan for Combating Antibiotic Resistant Bacteria 53 . However, drawbacks of capture probe enrichment, compared with untargeted approaches for infectious disease diagnosis, include a bias towards tar geted microorganisms, added steps, increased costs and long hybridization times (24-48 hours) as a result of the additional processing needed for maximal efficiency.…”
Section: Seroconversionmentioning
confidence: 99%
“…21 ) and for surveillance of antimicrobial resistance in the food supply by bacterial whole genome sequencing 22 . Increasingly, big data provided by mNGS is being leveraged for clinical purposes, including charac terization of antibiotic resistance directly from clinical samples 23 and analysis of human host response (tran scriptomic) data to predict causes of infection and evalu ate disease risk 24,25 . Thus, mNGS can be a key driver for precision diagnosis of infectious diseases, advancing precision medicine efforts to personalize patient care in this field.…”
mentioning
confidence: 99%
“…Provided suitable sensitivity can be achieved and data processing simplified, this is where rapidly evolving technologies such as next generation sequencing (NGS) may find tremendous application [56]. Several excellent studies have recently demonstrated use of targeted pyrosequencing and next generation sequencing approaches to rapid detect and identify both horizontally and vertically transmitted AMR determinants within Select Agent strains [57][58][59]. While these recent studies emphasized a limited number of AMR genes, we hope that these technologies will prove useful in performing similarly broad-based surveys of Select Agents and other pathogenic species.…”
Section: Discussionmentioning
confidence: 99%
“…For example, isolate shotgun sequencing information uncovered unexpected transmission routes during multi-drug resistant nosocomial organism outbreaks (Snitkin, Zelazny et al 2012, Roach, Burton et al 2015, Snitkin, Won et al 2017). Other studies showed use of targeted sequencing to group E. coli clonotypes from patient’s direct urine samples (Tchesnokova, Billig et al 2013), or to detect ciprofloxacin resistance markers (Stefan, Koehler et al 2016), resulting in antimicrobial susceptibility data and improvement in clinical outcome prediction. Finally, agnostic (unbiased, metagenomic) sequencing shows promise as a diagnostic of last resort where no other diagnostic can determine the infectious microorganism, such as the successful ID-NGS diagnosis of leptospira infection with resulting positive outcome for the patient (Wilson, Naccache et al 2014).…”
Section: Introductionmentioning
confidence: 99%